P192 Crystallising care: improving hospital gout management. (20th April 2020) - Clarke, Benjamin D; Russell, Mark D; Rutherford, Andrew I; Galloway, James B; Stack, John
Abstract: Background: Gout is the most common cause of a hot swollen joint, and a major contributor to inpatient rheumatology workload. Recently published data demonstrated that hospital admissions due to gout increased by 59% in England from 2006 - 2017. The mean length of stay for a gout admission was 6 days in 2017; a figure that has not changed significantly over the last decade. We hypothesised that a key contributing factor to prolonged hospital stays in patients presenting with gout attacks is delayed joint aspiration and synovial fluid analysis. We investigated time to joint aspiration, and time taken to obtain a crystal analysis result, in acute rheumatology referrals at a large tertiary centre. Methods: Electronic Health Records (EHR) system data were accessed for all joint aspirate crystal analyses in a 4-month window in 2017. EHR system documentation contains all clinical notes, electronic referrals, and laboratory requests with indicative coded timestamps. Pre- and post-aspirate differential diagnoses were compiled from the clinical record. Manual verification of the clinical records ascertained whether there was any delay in discharge pertaining to a crystal analysis. For representation, time figures were rounded to the nearest hour. Results: Over a 4-month period, 38 patients who had been referred to the inpatient rheumatology team at King's College Hospital had crystal analysis performed following joint aspiration; 24 from an emergency department setting, and 14 from an inpatient ward setting. The proportions of these cases by articular distribution (with the specific joint aspirated in brackets) were: 55% monoarthritis (knee), 16% oligoarthritis (knee), 16% polyarthritis (knee), 10% polyarthritis (wrist), 3% monoarthritis (elbow). Mean time from rheumatology referral to joint aspiration was 7 hours (range 1-21; median 5; IQR 3-8). The mean time from sample acquisition to crystal analysis result was 20 hours (range 1-95; median 16; IQR 4-21). Discharges for 17/38 (45%) patients were pending crystal analysis results, of which 10/17 (59%) patients were discharged without results. Rheumatology clinician pre-test diagnostic accuracy was 55%. Comparing pre-aspirate diagnosis with final diagnosis, proportionately septic arthritis was over-diagnosed, whilst gout was under-diagnosed. Conclusion: Gout remains a difficult condition to promptly differentiate and treat in hospital. Clinician workload and joint aspiration burden are rising due to global incidence trends. A move to establish a "7-day NHS" and significant bed pressures have developed since the British Society for Rheumatology (BSR) hot swollen joint guideline was published. In our centre, inadequate crystal diagnostics appear to be driving prolonged length of stay. Further evaluation of causal factors in the delay of recognition, referral and diagnostics is required. Through application of quality improvement methodology, process-mapping and driver diagrams we plan to implement a point-of-care testing (POCT) and door-to-needle (DTN) programme, researching how to improve the gout patient's experience. Disclosures: B.D. Clarke None. M.D. Russell None. A.I. Rutherford None. J.B. Galloway None. J. Stack None.